THE MEANING OF “BOUNDARY LINE” DUE TO THE PRECAST MODULE SYSTEM IN ‘RUSUNAWA’ BUMI CENGKARENG INDAH, JAKARTA, INDONESIA - Y. Basuki Dwisusanto; Fermanto Lianto; Lilianny Sigit Arifin (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2018)
This research reveals meaning of “boundary line” due to the precast module system in Seruni 8 block, ‘Rusunawa’ Bumi Cengkareng Indah, Jakarta, Indonesia. The Grounded Theory method, with the type of “constant comparison”, which is a semi-grounded theory, is chosen to express the meaning of the “boundary line” from the residents’ point of view. The coding process in data processing uses computer program Maxqda. The results of this study indicate that well-established relationships between occupants can transform the boundaries of private corridor ownership (individual territory) into joint ownership (communal territory) as a place to socialize and share goods placed in the corridor, and maintain the cleanliness of the corridor together, so that the “boundary line” due to the precast module system for residents of the Seruni 8 block, ‘Rusunawa’ Bumi Cengkareng Indah, Jakarta, does not affect the meaning of the boundaries as the individual territory, because the communal territory is stronger than the “boundary line” due to the precast module system.